DETECTION OF WSSV AND VIBRIO PARAHAEMOLYTICUS IN PENAEUS MONODON (FABRICIUS) USING DNA DOT-BLOT HYBRIDIZATION TECHNIQUE - Mishra, S S; BRAHMANE, Manoj P; Maurye, Praveen; Mali, P; Das, Manas Kumar (Journal of the Inland Fisheries Society of India, 2016)
Penaeus monodon, samples collected from different shrimp farms located in North 24 Parganas, West Bengal, were analyzed for detection of White Spot Syndrome Virus (WSSV) and Vibrio parahaemolyticus. Affected shrimp exhibited reddish body discoloration with necrosis of appendages. Minute white spots or patches on carapace and body cuticle were also visible. WSSV and V. parahaemolyticus DNA were amplified using PCR and the PCR amplified products were used as DNA probes. DNA dot blot hybridization using alkaline-phosphatase (AP) labelled DNA probes, specific for WSSV and V. parahaemolyticus detected DNA in tissue samples.